Validity of the PJBL-STEAM Teaching Module Containing Local Wisdom of Sasirangan Natural Dye to Increase Scientific Literacy - Arif Sholahuddin; Zainal Fuad (Green Publisher Indonesia, 2025)
PISA 2022 results show that Indonesia's scientific literacy is still low. This is because the learning resources containing local wisdom in learning are very limited. This research aims to analyze the validity of the PjBL-STEAM teaching module containing the local wisdom of natural dye to increase students' scientific literacy. The research method is design research using the ADDIE model with five stages, namely analyze, design, develop, implement, and evaluate. Stage 1) analyze, in the form of an analysis of the curriculum, student characteristics, and existing module products. Stage 2) design, which consists of designing the draft module and research instruments. Stage 3) develop, in the form of collecting validity data through assessments from three experts and two practitioners. Stages 4) implement and 5) evaluate will be carried out in further research. The research results obtained showed content validity of 3.54 (very valid), linguistic validity of 3.49 (very valid), presentation validity of 3.63 (very valid), graphic validity of 3.5 (very valid), and scientific literacy aspect validity of 3.6 (very valid). Based on the assessment results, the PjBL-STEAM module containing the local wisdom of natural dye is valid and can be used to increase students' scientific literacy.